2011
DOI: 10.1111/j.1399-0004.2011.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous missense mutation in WNT10B in familial split‐hand/foot malformation

Abstract: Split-hand/foot malformation (SHFM) is a rare limb developmental malformation, characterized by variable degree of median clefts of hands and feet due to the absence of central rays of extremities. To date, six different forms of SHFM have been described. Four of these SHFM1, SHFM3, SHFM4 and SHFM5 show autosomal dominant, SHFM6 autosomal recessive and SHFM2 X-linked pattern of inheritance. In this study a large consanguineous Pakistani family, with autosomal recessive SHFM, appeared in the last two generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Primer sequences for PCR-amplification of the WNT10B gene were the same as reported previously [Khan et al, 2012]. These sequences are available upon request.…”
Section: Pcr and Sanger Sequencingmentioning
confidence: 99%
“…Primer sequences for PCR-amplification of the WNT10B gene were the same as reported previously [Khan et al, 2012]. These sequences are available upon request.…”
Section: Pcr and Sanger Sequencingmentioning
confidence: 99%
“…Linkage or cytogenetic analysis of the nonsyndromic forms in humans has revealed six different loci for SHFM1-6 types: chromosome 7q21.2-q21.3 (SHFM1, MIM 183600), 4,5 Xq26 (SHFM2, MIM 313350), 6 10q24 (SHFM3, MIM 600095), [7][8][9][10] 3q27 (SHFM4, MIM 605289), 1 2q31 (SHFM5, MIM 606708) 11,12 and 12q13 (SHFM6, MIM 225300). 13,14 SHFM1, 3, 4 and 5 exhibit autosomal-dominant inheritance; SHFM6 exhibits autosomal-recessive transmission; SHFM2 exhibits X-linked inheritance pattern. 6,15,16 TP63 (also called P63, MIM603273) 17 encodes a homolog of the tumor suppressor p53 18 and is associated with both isolated and syndromic SHFM4.…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested the 300 kb region distal to the SHFM1 , DLX5 , and DLX6 genes and between BAC RP11-800O14 and marker D7S618 as a causative defect region for SHFM. However, a report by van Silfhout et al [7] (case 3) involving inv(7)(p22q21.3) showed typical SHFM without mutations in SHFM1 , DLX5 , or DLX6 . Our case and another case by van Silfhout et al [5] (case 2) harbored deletions spanning the three candidate genes and the above regions suggested by Tzschach et al [4], but they did not exhibit distinct ectrodactyly.…”
Section: Discussionmentioning
confidence: 97%
“…SHFM is a heterogeneous disorder that can occur in isolated nonsyndromic form or as one phenotype of several syndromes. To date, six different forms of nonsyndromic SHFM, deemed SHFM1-6, have been described in humans [7]. Of these, SHFM1 maps to 7q21q22, a region that spans several candidate genes, such as SHFM type 1 ( SHFM1 ), distal-less homeobox 5 ( DLX5 ), and distal-less homeobox 6 ( DLX6 ) [8].…”
Section: Discussionmentioning
confidence: 99%